Analisis Pengungkapan Diri Anak Sekolah Dasar di Media Sosial Instagram - Christy, Graciella Lawrence; Sari, Dewi Kartika; Herwandito, Seto (Universitas Pahlawan Tuanku Tambusai, 2024)
Instagram can now be accessed by anyone, including elementary school children. With that convinience, there are negative impacts in it. Children are not yet able to sort out what content is available. Self disclosure by children can be in the form of hobby posts to their emotions in the features on Instagram. This study aims to determine the ways and reasons for elementary school children in self disclosure on instagram. This research uses a qualitative approach with an exploratory type of approach and using social penetration theory with four stages from superficial relationships to more intimate relationships.